Strategi Pengembangan Penangkaran Benih Melalui Kegiatan Desa Mandiri Benih - Lagga, Jamaluddin; Azis Ambar, Abdul; Abdullah, Abdullah (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Rice is the primary staple food source for most of Indonesia's population. Rice is a strategic commodity that is quite significant for the State's social, economic, political, and even security aspects to meet food needs and sustainable self-sufficiency targets; substantial efforts are needed, namely by the quality of seeds strongly influences increasing productivity and increasing productivity and the quality of plant products. Breeding seeds through the Desa Mandiri Benih activity is one of the efforts to meet the needs of seeds and solve seed problems at the farmer level. The objectives of this study were: To analyze the influencing factors and formulate appropriate strategies for developing independent village seed breeder groups in Watang Pulu District, Sidenreng Rappang Regency. This research was conducted for 2 (two) months, from December 2020 to January 2021. The research sample was 8 people, including Bureaucracy, Extension and Farmer group members. The analysis used is the analysis of internal and external factors, SWOT strategy and QSPM analysis. The results showed that the internal and external factors that influenced the development of seed breeding were good production results, limited capital, increased awareness of farmers about the use of certified seeds and pests and diseases. The analysis results are three strategic priorities: Increasing seed production and establishing partnerships with seed companies, Optimizing group potential by improving captive facilities and infrastructure, and Improving coordination with relevant agencies and extension workers to facilitate the development of seed breeding.